Second nature [large type]: a love story - Mitchard, Jacquelyn (Center Point Pub., 2011)
Losing her father in a school fire that disfigures her face, Sicily is raised by a dynamic aunt who urges her to pursue a normal life, an effort that is influenced by her fiancé, a terrible drunken revelation and an opportunity for a risky full-face transplant.